Knee and Hip Extension Responses to Prolonged Simulated Soccer Match-Play: a 2D Study - Hamdan, Muhammad; Norfariza Mohd Noha, Siti; Hasan, Hosni; Ismail, Hashbullah; Mohammed Firhad Raja Azidin, Raja (International Journal of Engineering and Technology, 2018)
The first part of this study was a reliability study to compare inter-software, inter- and intra- tester measurements using intraclass correlation coefficients (ICC2,1). All, ICC2,1 values showed excellent scores thus supporting the utility of a two dimensional motion analysis system using an open-source, free software. In the second part of this study, the effects of a 120-minute simulated match-play simulation on knee and hip kinematic was investigated. Eighteen participants consented to this study and were required to complete a 120 minutes of simulated soccer match-play. Knee and hip angles were measured at initial contact during 45Â° anticipated side-cutting tasks throughout the simulation. A 2 Ã— 7 SPANOVA was utilized. Both knee and hip extension angles were significantly altered over time. No significant differences were observed between dominant and non-dominant sides. A more extended knee and hip landing posture suggested a greater risk of ACL injury during match-play over time. Findings from this study suggest that the non-dominant limb is as likely to suffer non-traumatic ACL injury as the dominant limb. Further interrogations of the biomechanical differences in the knees and hips across limb dominance are warranted for more comprehensive understanding of the changes in multiplanar perspectives following fatigue inducing exertions.Â Â